Determination of Three Preservatives in Food by Ultrahigh Conductivity Zone-Low Temperature Zone/Sweeping-Micellar Electrokinetic Chromatography in Non-Aqueous Capillary Electrophoresis - Huang1, Wen-Yi; Sun1, Ke; Li1, Li-Jun; Zhang1, Rui-Rui; Luo1, Ying; Hu1, Da-Chun; Deng1, Chun-Yan; Li1, Yan-Qing (Asian Journal of Chemistry, 2014)
An ultrahigh conductivity zone-low temperature zone (UHCZ-LTZ)/sweeping-micellar electrokinetic chromatography (MEKC) method was used for the simultaneous separation and determination of three preservatives i.e., benzoic acid, sorbic acid and dehydroacetic acid in food. The result indicated that a best separation of the three preservatives was obtained on a uncoated fused silica capillary column (50 cm × 50 μm, effective length 36 cm) by using the background electrolyte containing 50 mmol/L ammonium acetate (CH3COONH4), 6 mmol/L sodium hydroxide (NaOH), 6 mmol/L cetyltrimethyl ammonium bromide (CTAB) and 10 % acetonitrile (CH3CN) (by volume) in methanol. The detection wavelength was set at 230 nm, separation voltage was -22 kV, sample injection voltage was -20 kV and injection time was 8 s, injection time of high-conductivity zone was 15 s. Under the optimum conditions, the three preservatives was performed within 20 min with relative standard deviation (RSDs) of peak area less than 5 %. The detection limits (S/N = 3) of benzoic acid, sorbic acid and dehydroacetic acid were 0.61, 0.361 and 0.999 ng/mL, respectively.